Implementation of Sustainable Tourism Based on Community Based Tourism as a Pillar of Development in Waturaka Village, Kelimutu District - Andrinata, Andrinata (English and Tourism Studies, 2024)
Sustainable tourism activities involve interactions between local community members and tourists. One of the concepts applied in sustainable tourism development is Community-Based Tourism. This concept emphasizes the contribution and active participation of local communities in developing the tourism industry. The research method employed is qualitative, utilizing field research. Data analysis techniques follow the interactive model of Miles and Huberman, which includes data collection, reduction, presentation, and conclusion drawing. Community participation in tourism activities in Waturaka Village primarily involves labor, expertise, and skills contributed by each resident. Residents participating in tourism activities form groups such as tourism awareness groups (Pokdarwis), farming groups, homestay groups, art groups, craftspeople groups, and tour guide groups.